Energy use and Economic Growth in Africa: A Panel Granger-Causality Investigation - (:unkn) unknown (My University, 2014)
We make use of a bootstrap panel analysis of causality between energy use and economic growth for a sample of sixteen African countries over the period 1988-2010. Our results show that growth and energy use are strongly linked in Africa. However, African countries are heterogeneous and there is no "one way" recommendation about energy-growth relationship that may work for all countries in Africa.
Keywords: African Research